The Encyclopedia of Applied Linguistics 2020
DOI: 10.1002/9781405198431.wbeal0768.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Mobile‐Assisted Language Learning

Abstract: Mobile‐assisted language learning (MALL) is the use of smartphones and other mobile technologies in language learning, especially in situations where portability and situated learning offer specific advantages. A key attraction of mobile learning is the ubiquity of mobile phones. Typical applications can support learners in reading, listening, speaking, and writing in the target language, either individually or in collaboration with one another. Increasingly, MALL applications relate language learning to a per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 21 publications
0
19
0
1
Order By: Relevance
“…MALL refers to “the use of smart phones and other mobile technologies in language learning, especially in situations where portability and situated learning offer specific advantages” (Kukulska‐Hulme, 2013, p. 1). Three decades of research has shown the benefits of MALL (Burston, 2014, 2015) such as promoting collaborative language learning (Kukulska‐Hulme & Viberg, 2018) and fostering formal and informal language practice (Hsu, 2013; Kolb, 2006; Wagner & Wilson, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…MALL refers to “the use of smart phones and other mobile technologies in language learning, especially in situations where portability and situated learning offer specific advantages” (Kukulska‐Hulme, 2013, p. 1). Three decades of research has shown the benefits of MALL (Burston, 2014, 2015) such as promoting collaborative language learning (Kukulska‐Hulme & Viberg, 2018) and fostering formal and informal language practice (Hsu, 2013; Kolb, 2006; Wagner & Wilson, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Three decades of research has shown the benefits of MALL (Burston, 2014, 2015) such as promoting collaborative language learning (Kukulska‐Hulme & Viberg, 2018) and fostering formal and informal language practice (Hsu, 2013; Kolb, 2006; Wagner & Wilson, 2005). These benefits can be attributed at least in part to the typical features of MALL, including accessibility–easy and spontaneous access to language learning resources and activities, continuity–smooth learning transfer across devices and learning platforms, flexibility–flexible time and space for learning, and adaptability–easy alignment to personal learning habits (Kukulska‐Hulme, 2013; Loewen et al ., 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies like this encourage innovation and development of mobile application and features which will be powerful for learning English in ESL and EFL contexts. An extensive study found that MALL is powerful for varying English teaching and learning activity which is flexible and dynamic and giving the opportunity to teachers, researchers and application makers to develop the best smartphone applications for learning English [23].…”
Section: Mobile-assisted Language Learningmentioning
confidence: 99%
“…Determining the best strategies for successfully implementing mobile devices to improve learning is an important issue that need intense study especially in integrating m-learning into classroom environments. M-learning is proving its potential to address authentic learner needs at the point at which they arise [35].…”
Section: Future Work and Conclusionmentioning
confidence: 99%